Metode Bercakap-Cakap Bagi Anak Usia Dini: METODE BERCAKAP-CAKAP BAGI ANAK USIA DINI - Elfan Fanhas F Kh (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2016)
Early Childhood is a golden age phase to transformation of basic knowledge and basic value, but few among us understand and take advantage of that opportunities cause lack of knowledge and method to educate early childhood. Al-Qur`an as a way of life for all mankind from his creator give an over view about an effective learning methods based on the characteristics of early childhood, that is chatting methods. Based on descriptive analysis of Al-Qur`an surah Al-Baqarah 30-33 it`s contains dialogue between Allah S.W.T., with angels about the first creation of human being. Chatting methods are as follows : (1). Do stimulation or impulse of curiosity (2). Answer the questions untill the child stopped to ask (3). Give a new insights in your answer (4). Concrete your answers (5). Give the questions back.